INTERNATIONAL COLLABORATION PROGRAM: EDUCATIONAL GAME ACTIVITIES TO ENHANCE STUDENTS' CREATIVITY, TOGETHERNESS, AND LEARNING ENTHUSIASM AT SEKOLAH KEBANGSAAN TANJUNG SURAT, JOHOR, MALAYSIA - Harahap, Dahrul Aman; Yesa, Hesti Desba; Gaol, Lestari Herlina Lumban; Mokerje, Nadya Febriani; Utama, Yolanda Sa'ad; Ardhana, Alzeyna Dwilovita; Putra, Sulfanow; Dewi, Hanindianti; Borgias, Frans; Ridho Harahap, Rasyid; Wibowo, Agung Edy; Harefa, Selamat Kristian; Wibowo, Edwin Agung; Hasibuan, Rahman (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
The international collaboration program through educational game activities at Sekolah Kebangsaan Tanjung Surat, Johor, Malaysia, was designed to enhance three key outcomes: students’ creativity, togetherness, and learning enthusiasm. The intervention was carried out through a series of collaborative educational games (such as word guessing, puzzles, role-play, and team relays) facilitated by cross-country instructors. The implementation results indicated an increase in active participation, positive social interactions among students, as well as the emergence of creative ideas in problem-solving and group presentations. These findings highlight that a structured and contextual play-based learning approach is effective in strengthening students’ intrinsic motivation and socio-cognitive competencies within a multicultural school environment. Recommendations include institutionalizing educational game sessions within the school calendar, conducting joint facilitator training, and establishing periodic evaluations based on creativity, teamwork, and learning engagement indicators.